Isolation of reovirus T3D mutants capable of infecting human tumor cells independent of junction adhesion molecule-A. - Diana J M van den Wollenberg (Public Library of Science (PLoS), 2012)
Mammalian Reovirus is a double-stranded RNA virus with a distinctive preference to replicate in and lyse transformed cells. On that account, Reovirus type 3 Dearing (T3D) is clinically evaluated as oncolytic agent. The therapeutic efficacy of this approach depends in part on the accessibility of the reovirus receptor Junction Adhesion Molecule-A (JAM-A) on the target cells. Here, we describe the isolation and characterization of reovirus T3D mutants that can infect human tumor cells independent of JAM-A. The JAM-A-independent (jin) mutants were isolated on human U118MG glioblastoma cells, which do not express JAM-A. All jin mutants harbour mutations in the S1 segments close to the region that encodes the sialic acid-binding pocket in the shaft of the spike protein. In addition, two of the jin mutants encode spike proteins with a Q336R substitution in their head domain. The jin mutants can productively infect a wide range of cell lines that resist wt reovirus T3D infection, including chicken LMH cells, hamster CHO cells, murine endothelioma cells, human U2OS and STA-ET2.1 cells, but not primary human fibroblasts. The jin-mutants rely on the presence of sialic-acid residues on the cell surface for productive infection, as is evident from wheat germ agglutinin (WGA) inhibition experiments, and from the jin-reovirus resistance of CHO-Lec2 cells, which have a deficiency of sialic-acids on their glycoproteins. The jin mutants may be useful as oncolytic agents for use in tumors in which JAM-A is absent or inaccessible.